\(x^2-5x+6=0\)
\(\Leftrightarrow x^2-2x-3x+6=0\)
\(\Leftrightarrow x.\left(x-2\right)-3.\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right).\left(x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=2\\x=3\end{cases}}}\)
Vậy ....
\(x^2-5x+6=0\)
\(\Leftrightarrow\)\(x^2-2x-3x+6=0\)
\(\Leftrightarrow\)\(x\left(x-2\right)-3\left(x-2\right)=0\)
\(\Leftrightarrow\)\(\left(x-2\right)\left(x-3\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x-2=0\\x-3=0\end{cases}}\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=2\\x=3\end{cases}}\)
Vậy...